Polypropylene composite material, and preparation method and application thereof

By adding aluminum oxynitride and magnesium aluminum spinel fillers and toughening agents to polypropylene materials, a physical barrier layer is formed, which solves the problems of high shrinkage, poor solvent resistance and low light transmittance of polypropylene materials. This achieves comprehensive performance of high dimensional stability, solvent resistance and light transmittance, and is suitable for parts such as automotive bumpers.

CN119775660BActive Publication Date: 2026-11-06WUHAN JINFA TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411915074.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2026-11-06
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing polypropylene materials suffer from problems such as high shrinkage, poor solvent resistance, and low light transmittance. In particular, they are prone to whitening during the painting process after laser engraving, which affects the aesthetics and light transmittance.

Method used

Aluminum oxynitride and magnesium aluminum spinel are used as fillers and combined with toughening agents to form a physical barrier layer through their low linear expansion coefficient and isotropic characteristics, thereby improving the dimensional stability and solvent resistance of the material. At the same time, fillers with an average particle size of 2-5 μm are selected to maintain light transmittance.

Benefits of technology

It achieves high dimensional stability, solvent resistance and light transmittance of polypropylene composite materials, meets the requirements of painting after laser engraving, avoids whitening, and is suitable for large parts such as car bumpers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the field of polypropylene materials, and specifically discloses a polypropylene composite material, a preparation method and application thereof.A polypropylene composite material comprises the following components in parts by weight: 49-71 parts of polypropylene, 8-32 parts of a filler, 4-31 parts of a toughening agent, and 0.4-1.1 parts of an auxiliary agent; the filler comprises at least one of aluminum oxynitride and magnesium aluminum spinel; and the average particle size of the filler is 2-5 microns.In the polypropylene composite material, the filler with a specific particle size and the toughening agent cooperate with each other, significantly improving the dimensional stability, solvent resistance and light transmittance of the polypropylene composite material, so that the polypropylene composite material has the comprehensive performance of high dimensional stability, solvent resistance and light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polypropylene materials, specifically relating to a polypropylene composite material, its preparation method, and its application. Background Technology

[0002] Polypropylene (PP) boasts advantages such as low density, low cost, and ease of processing. As a semi-transparent polymer material with a light transmittance of approximately 50-80%, it is widely used in translucent automotive interior and exterior components. However, high-transmittance PP is inherently brittle and has poor toughness. In this field, rubber-phase elastomers are typically added to improve brittleness and toughness. However, elastomers negatively impact the light transmittance, reducing it. Furthermore, currently available translucent PP composites generally suffer from poor dimensional stability, exhibiting large shrinkage rates, typically exceeding 1%. For example, large parts like bumpers exhibit significant dimensional changes, clearly failing to meet assembly requirements and hindering practical application. Therefore, current methods involve adding inorganic fillers or modifying the material to improve dimensional stability. However, the high density and poor compatibility of fillers with the matrix significantly reduce light transmittance. In addition, existing transparent PP materials also suffer from poor solvent resistance. Especially when laser engraving is applied to the surface of a transparent polypropylene bumper, the primer will physically swell with the bumper substrate during painting, causing severe whitening at the laser engraving location. This not only affects the overall aesthetics of the bumper but also the light transmission of the laser engraving pattern. Summary of the Invention

[0003] In view of the shortcomings of the existing polypropylene materials mentioned above, such as large shrinkage, poor solvent resistance, and low light transmittance, the present invention will provide a polypropylene composite material, its preparation method, and its application.

[0004] To achieve the above objectives, the following technical solutions are specifically included: On one hand, the present invention provides a polypropylene composite material comprising the following components in parts by weight: The composition includes 49-71 parts polypropylene, 8-32 parts filler, 4-31 parts toughening agent, and 0.4-1.1 parts additives. The filler includes at least one of aluminum oxynitride and magnesium aluminum spinel. The average particle size of the filler is 2-5 μm.

[0005] In the polypropylene material of this invention, at least one of aluminum oxynitride and magnesium aluminum spinel is used as a filler. Utilizing its low linear expansion coefficient and isotropic properties, it works in conjunction with a toughening agent to reduce the material's shrinkage rate and improve its dimensional stability. Simultaneously, based on the physical barrier and chemical stability of the filler, a physical barrier layer is formed on the material surface, preventing chemical reagents from penetrating and swelling the toughening agent, thus improving the material's solvent resistance and meeting the requirements for painting after laser engraving. Furthermore, since both aluminum oxynitride and magnesium aluminum spinel are visible light-transmitting materials, they not only do not significantly reduce the material's transmittance, but also, due to the different dispersibility, light scattering, refraction, and transmission effects of fillers with different particle sizes, the inventors of this invention have found that selecting fillers with an average particle size of 2-5 μm can significantly improve the material's transmittance. Therefore, the polypropylene composite material of this invention can comprehensively achieve high dimensional stability, solvent resistance, and transmittance.

[0006] Preferably, the polypropylene composite material comprises the following components in parts by weight: 50-70 parts polypropylene, 10-30 parts filler, 5-30 parts toughening agent, and 0.5-1 parts additives, wherein the filler includes at least one of aluminum oxynitride and magnesium aluminum spinel. Common polypropylene resins in the art can be used in this invention, including but not limited to at least one of homopolymer polypropylene, random copolymer polypropylene, and block copolymer polypropylene.

[0007] Preferably, the melt mass flow rate (MFR) of the polypropylene tested according to ISO 1133-2011 at 230°C and 2.16 kg load is 19-55 g / 10 min, specifically 19 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range. The polypropylene of the present invention may specifically include, but is not limited to, copolymer polypropylene with a melt flow rate of 19-55 g / 10 min tested at 230°C and 2.16 kg load according to ISO 1133-2011, random copolymer polypropylene with a melt flow rate of 19-55 g / 10 min tested at 230°C and 2.16 kg load according to ISO 1133-2011, and block copolymer polypropylene with a melt flow rate of 19-55 g / 10 min tested at 230°C and 2.16 kg load according to ISO 1133-2011.

[0008] The polypropylene resin of the present invention has a mass percentage content of not less than 40% in the polypropylene composite material, more preferably not less than 50%, and even more preferably not less than 70%.

[0009] Preferably, the filler comprises aluminum oxynitride and magnesium aluminum spinel, with a mass ratio of aluminum oxynitride to magnesium aluminum spinel of (5-14):(1-10). The specific mass ratio of aluminum oxynitride to magnesium aluminum spinel can be 5:1, 5:5, 5:10, 10:1, 10:5, 14:1, 14:5, 14:10, etc., as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0010] Different fillers have different effects on the light transmittance of polypropylene composites. The inventors of this invention have found that, preferably, when aluminum oxynitride and magnesium aluminum spinel are used as a composite filler, the dimensional stability and light transmittance of the polypropylene composite are better than when aluminum oxynitride or magnesium aluminum spinel are used alone.

[0011] Preferably, the toughening agent includes at least one of ethylene-butene copolymer, ethylene-octene copolymer (POE), and hydrogenated styrene-butadiene block copolymer (SEBS).

[0012] Preferably, the toughening agent, tested according to ASTM D1238 at 190°C and a 2.16 kg load, has a melt flow rate of 1-13 g / 10 min, specifically 1 g / 10 min, 3 g / 10 min, 6 g / 10 min, 9 g / 10 min, 12 g / 10 min, 13 g / 10 min, etc., and specific values ​​between these ranges. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range. The toughening agent of this invention is generally an elastomer. The inventors of this invention have discovered that the toughening agent can significantly increase the toughness of polypropylene composite materials, and in combination with fillers, reduces shrinkage, which is beneficial for improving solvent resistance and light transmittance.

[0013] This invention uses laser diffraction to test the average particle size of the filler. The average particle size of the filler can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0014] Preferably, the additives include at least one of antioxidants, weather-resistant agents, and lubricants.

[0015] More preferably, the lubricant includes at least one of amide lubricants and stearic acid lubricants.

[0016] More preferably, the antioxidant includes at least one of hindered phenolic antioxidants and phosphite antioxidants.

[0017] More preferably, the weathering agent includes at least one of o-hydroxybenzophenone, benzotriazole, salicylates, triazine, substituted acrylonitrile, and hindered amine light stabilizers.

[0018] In this invention, other (functional) additives may be added as needed, such as, but not limited to, antioxidants, weather-resistant agents, and lubricants. Conventional antioxidants, weather-resistant agents, and lubricants in the art can be used in this invention to increase the functionality of polypropylene composites and improve their overall performance.

[0019] On the other hand, the present invention provides a method for preparing the polypropylene composite material, comprising the following steps: mixing the raw materials evenly, and sequentially performing melt extrusion and granulation to obtain the polypropylene composite material.

[0020] Preferably, the temperature of the melt extrusion is 180-230°C.

[0021] In addition, the present invention also provides an automotive part prepared according to the aforementioned polypropylene composite material, wherein the automotive part is laser-engraved and then painted.

[0022] The polypropylene composite material of the present invention has high dimensional stability, solvent resistance and light transmittance, and is especially suitable for the preparation of painted car bumpers, ambient lights and other automotive parts. It can not only meet the basic requirements of dimensional stability of large parts, but also meet the transparency requirements of paint after laser engraving.

[0023] Compared with the prior art, the present invention has the following beneficial effects: In the polypropylene composite material of the present invention, the filler and toughening agent of specific particle size work together to significantly improve the dimensional stability, solvent resistance and light transmittance of the polypropylene composite material, so that the polypropylene composite material has the comprehensive performance of high dimensional stability, solvent resistance and light transmittance. Detailed Implementation

[0024] To better illustrate the purpose, technical solution, and advantages of the present invention, specific embodiments will be used to further explain the invention below. Unless otherwise specified, all raw materials used in the embodiments and comparative examples of the present invention are commercially available, and the same raw materials were used in all parallel experiments.

[0025] (1) Polypropylene: PP-1: SZ30S, melt flow rate 30g / 10min, Sinopec; PP-2: H9018, melt mass flow rate 55 g / 10 min, Lanzhou Petrochemical; PP-3: RP346R, melt flow rate 19 g / 10 min, CNOOC Shell; (2) Transparent ceramic materials Aluminum oxynitride 1: Powder with an average particle size of 3μm obtained through sieving; Toplink Technology; Aluminum oxynitride 2: Powder with an average particle size of 2μm obtained by sieving; Toplink Technology; Aluminum oxynitride 3: Powder with an average particle size of 5μm obtained through sieving; Toplink Technology; Aluminum oxynitride 4: Powder with an average particle size of 1μm obtained by sieving; Toplink Technology; Aluminum oxynitride 5: After sieving, the average particle size was 6μm. (Topli Technology) Magnesium aluminum spinel: Magnesium aluminum spinel (MgAl6O 10 Single-crystal substrates, after sieving to obtain powder with an average particle size of 3μm, Hubei Baoling Chemical Technology Co., Ltd. Alumina: Powder with an average particle size of 3μm obtained through sieving; Qinghe County Ruijiang Metal Materials Co., Ltd. (3) Toughening agent: Toughening agent 1: Ethylene-butene copolymer, POE 7447, melt flow rate 5 g / 10 min, Dow; Toughening agent 2: Ethylene-butene copolymer, POE 7467, melt flow rate 1.2 g / 10 min, Dow; Toughening agent 3: Ethylene-butene copolymer, POE 7256, melt flow rate 2 g / 10 min, Dow; Toughening agent 4: Ethylene octene copolymer, POE 8137, melt flow rate 13 g / 10 min, Dow; Toughening agent 5: Hydrogenated styrene-butadiene front copolymer, SEBS 7551, melt flow rate 5 g / 10 min, Lee Chang-jung, Taiwan, China; (4) Antioxidants: Antioxidants: The antioxidants are SONOX 1010 and SONOX 168 in a 1:1 mass ratio, both of which are commercially available; (5) Lubricant: Ethylene bis-stearamide, commercially available; (6) Weathering agent: hindered amine light stabilizer T-81, commercially available.

[0026] Examples 1-17 and Comparative Examples 1-5 A polypropylene composite material, the preparation method of which includes the following steps: (1) Add all raw materials except fillers to the high-speed mixer according to the proportions of each raw material in Table 1-2 and mix them thoroughly. Then add the mixed material to the extruder through the main feed port. (2) The transparent ceramic material is added through the side feed port. The length-to-diameter ratio of the extrusion screw is 36-48:1. After mixing, melting and homogenizing, the material is extruded and granulated. The extruder temperature is set as follows: Zone 1 80-120℃, Zones 2-5 180-200℃, and other zones 200-230℃. After granulation, the polypropylene composite material is obtained.

[0027] Table 1 Table 2 To verify the performance of the polypropylene composite material described in this invention, the polypropylene composite materials prepared in the examples and comparative examples were subjected to performance tests. The specific test methods and acceptance criteria are as follows: (1) Solvent resistance: The polypropylene composite materials of the above examples and comparative examples were injection molded into 210×150mm samples according to conventional processes. Laser engraving was performed on the surface of the samples, and then a solvent resistance test was conducted with a transparent primer. The degree of whitening of the sample and the transparent primer was observed and divided into three levels: no whitening (A), slight whitening (B), whitening and swelling whitening (C). Level B and above are considered qualified. (2) Dimensional stability: The polypropylene composite materials of the above examples and comparative examples were injection molded into rectangular templates of 200×50mm (formed in the injection mold cavity) according to conventional processes, and annealed at 90℃ for 2 hours. The dimensional changes before and after annealing were measured by vernier calipers to calculate the shrinkage rate and evaluate its dimensional stability. The smaller the shrinkage rate, the better the dimensional stability. The formula for calculating the shrinkage rate is: (L0-L) / L0×100%, where L0 is the length dimension of the injection mold cavity (i.e., before annealing), and L is the actual length dimension of the injection molded template after annealing. A shrinkage rate ≤1% is considered qualified. (2) Light transmittance: The polypropylene composite materials of the above examples and comparative examples were injection molded into 150×100×3mm samples according to conventional processes. The light transmittance was tested with reference to GB / T 2410-2008 standard. A light transmittance of ≥50% was considered qualified.

[0028] Table 3 As can be seen from the above embodiments, the polypropylene composite material of the present invention does not exhibit defects such as whitening and swelling whitening after laser engraving and painting. The shrinkage rate of the polypropylene composite material is less than or equal to 1%, and the light transmittance is ≥50%. Therefore, the polypropylene composite material of the present invention combines good solvent resistance, dimensional stability, and light transmittance.

[0029] In Examples 7, 4, 1, 5, and 6, the content of aluminum oxynitride gradually decreases (conversely, the content of magnesium aluminum spinel gradually increases). Examples 7, 4, 1, and 5, containing aluminum oxynitride, all have a solvent resistance grade of A, while Example 6, without aluminum oxynitride, has a solvent resistance grade of B. Comparing Examples 1 and 4-7 with Comparative Example 1, which lacks either magnesium aluminum spinel or aluminum oxynitride as filler, it can be found that both magnesium aluminum spinel and aluminum oxynitride can improve the solvent resistance of the polypropylene composite material, with aluminum oxynitride providing a greater improvement. Furthermore, comparing Examples 1 and 4-7 with Comparative Example 2, where only aluminum oxide is used as filler, the effect of aluminum oxide in improving the solvent resistance of the system of this invention is poor and cannot meet practical requirements. It is evident that different types of fillers have a significant impact on the solvent resistance of polypropylene composite materials. The system of this invention can only achieve good solvent resistance and meet the solvent resistance requirements of laser engraving and painting when using at least one filler, either magnesium aluminum spinel or aluminum oxynitride.

[0030] As the content of aluminum oxynitride gradually decreased in Examples 7, 4, 1, 5, and 6 (conversely, the content of magnesium aluminum spinel gradually increased), the shrinkage of the polypropylene composite material first decreased and then increased. Comparing Examples 1 and 4-7 with Comparative Example 1, which did not contain either magnesium aluminum spinel or aluminum oxynitride, it can be found that both magnesium aluminum spinel and aluminum oxynitride can improve the dimensional stability of the polypropylene composite material, with aluminum oxynitride improving dimensional stability to a greater extent. Furthermore, the combination of the two results in even better dimensional stability of the polypropylene composite material. Comparing Examples 1 and 4-7 with Comparative Example 2, which used only aluminum oxide as filler, the effect of aluminum oxide in improving the shrinkage rate of the system of the present invention is poor and cannot meet practical requirements. It is evident that different types of fillers have a significant impact on the shrinkage performance of polypropylene composite materials. The system of the present invention can only achieve good dimensional stability when using at least one filler, such as magnesium aluminum spinel or aluminum oxynitride.

[0031] As the content of aluminum oxynitride gradually decreased in Examples 7, 4, 1, 5, and 6 (conversely, the content of magnesium aluminum spinel gradually increased), the light transmittance of the polypropylene composite material first increased and then decreased. Comparing Examples 1 and 4-7 with Comparative Example 1 (without either magnesium aluminum spinel or aluminum oxynitride filler), it can be found that both magnesium aluminum spinel and aluminum oxynitride can improve the light transmittance of the polypropylene composite material, with aluminum oxynitride having a greater effect. Furthermore, the combination of the two results in even better light transmittance for the polypropylene composite material. Comparing Examples 1 and 4-7 with Comparative Example 2 (with only aluminum oxide filler), the effect of aluminum oxide filler on improving the light transmittance of the system of this invention is poor and cannot meet practical requirements. It is evident that different types of fillers can significantly affect the light transmittance of the polypropylene composite material. The system of this invention can only achieve good light transmittance when using at least one filler, such as magnesium aluminum spinel or aluminum oxynitride.

[0032] In Comparative Examples 4, 2, 1, 3, and 5, the average particle size of aluminum oxynitride gradually increases. The solvent resistance in Examples 1-3 and Comparative Example 5 all reached Grade A. In Comparative Example 4, the average particle size of aluminum oxynitride was too small, resulting in poor physical barrier properties and an inability to significantly improve the solvent resistance of the polypropylene composite. Shrinkage initially decreased and then increased with increasing average particle size of aluminum oxynitride, but dimensional stability was acceptable within the 1-6 μm range. Light transmittance initially increased and then decreased with increasing average particle size of aluminum oxynitride; only when the average particle size was within the 2-5 μm range was the light transmittance acceptable. Both excessively small and large average particle sizes significantly reduced the light transmittance of the material. Therefore, this invention can only achieve good solvent resistance and light transmittance simultaneously when using fillers with an average particle size of 2-5 μm.

[0033] As shown in Examples 1 and 3, toughening agents can significantly improve the dimensional stability and light transmittance of polypropylene composites. As shown in Examples 1 and 8-13, the melt flow rate and type of elastomer toughening agent have little effect on the solvent resistance, dimensional stability, and light transmittance of polypropylene composites. However, the toughening agent content should not be too high. Excessive toughening agent will exceed the dispersion threshold of the system, resulting in poor physical barrier properties in the system, which will reduce solvent resistance and light transmittance.

[0034] Comparing Example 1 with Comparative Examples 1-3, it can be seen that in the system of the present invention, the absence of either filler or toughening agent makes it impossible to simultaneously achieve solvent resistance, dimensional stability and light transmittance. Only when specific types and sizes of fillers and toughening agents are present in the system can better solvent resistance, dimensional stability and light transmittance be achieved.

[0035] As can be seen from Examples 1 and 16-17, the melt flow rate has little effect on the solvent resistance and dimensional stability of the polypropylene composite material. As the melt flow rate increases, the light transmittance first increases slightly and then decreases slightly. Therefore, when the melt flow rate is 19-55 g / 10 min, the light transmittance of the polypropylene composite material is better.

[0036] In summary, this invention addresses the issue of dimensional stability in large components such as translucent bumpers by introducing magnesium aluminum spinel and / or aluminum oxynitride from transparent ceramics in combination with an elastomer toughening agent. This leverages the low linear expansion coefficient and isotropic properties of these transparent ceramics, along with the increased compatibility and toughness of the toughening agent, to reduce post-shrinkage of the polypropylene composite material. Furthermore, the specific particle size of magnesium aluminum spinel and / or aluminum oxynitride, with its good physical barrier properties and chemical stability, allows the polypropylene composite to form a physical barrier layer on the surface of the injection-molded part, preventing chemical reagents from penetrating and swelling the elastomer toughening agent, thus improving solvent resistance. Moreover, since both aluminum oxynitride and magnesium aluminum spinel are transparent to visible light, they do not significantly reduce the material's transmittance. Moreover, due to the varying dispersion, light scattering, refraction, and transmission effects of fillers with different particle sizes, this invention maintains high light transmittance in the polypropylene composite when using magnesium aluminum spinel and / or aluminum oxynitride with an average particle size of 2-5 μm.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A polypropylene composite material, characterized in that, It includes the following components in parts by weight: The composition includes 49-71 parts polypropylene, 8-32 parts filler, 4-31 parts toughening agent, and 0.4-1.1 parts additives. The filler includes at least one of aluminum oxynitride and magnesium aluminum spinel. The average particle size of the filler is 2-5 μm. The toughening agent includes at least one of ethylene-butene copolymer, ethylene-octene copolymer, and hydrogenated styrene-butadiene block copolymer.

2. The polypropylene composite material as described in claim 1, characterized in that, The filler comprises aluminum oxynitride and magnesium aluminum spinel, with a mass ratio of aluminum oxynitride to magnesium aluminum spinel of (5-14):(1-10).

3. The polypropylene composite material as described in claim 1, characterized in that, The toughening agent, tested according to ASTM D1238 at 190°C and 2.16 kg load, has a melt flow rate of 1-13 g / 10 min.

4. The polypropylene composite material as described in claim 1, characterized in that, The polypropylene was tested according to ISO 1133-2011 at 230°C and 2.16 kg load, and the melt flow rate was 19-55 g / 10 min.

5. The polypropylene composite material as described in claim 1, characterized in that, The additives include at least one of antioxidants, weather-resistant agents, and lubricants.

6. The polypropylene composite material as described in claim 5, characterized in that, The antioxidant includes at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant includes at least one of amide lubricants and stearic acid lubricants; the weathering agent includes at least one of o-hydroxybenzophenones, benzotriazoles, salicylates, triazines, substituted acrylonitriles, and hindered amine light stabilizers.

7. A method for preparing the polypropylene composite material according to any one of claims 1-6, characterized in that, The process includes the following steps: mixing the raw materials evenly, and then sequentially performing melt extrusion and granulation to obtain the polypropylene composite material.

8. An automotive part made of polypropylene composite material according to any one of claims 1-6.

Citation Information

Patent Citations

  • Sand-plastic composite material with effect of releasing negative ions and preparation method of sand-plastic composite material

    CN109776903A

  • High-toughness conductive nylon material and preparation method thereof

    CN114685976A